ANALISIS REWARD AND PUNISHMENT TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV JAJANAN PREMIUM NUSANTARA - Andi Batary Citta; Andi Sri Kumala Putri; Sukmatica Slamet (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
Reward and punishment on work productivity, this study aims to identify the impact of reward and punishment on work productivity at CV Jajanan Premium Nusantara. This research method is quantitative, using questionnaires, interviews, and observations as data collection tools. the population numbered 158 and the sample participating in this study were 83 people, and were selected using the probability sampling method. The data used includes primary and secondary data, and data analysis was performed using SPSS software. The results of the study show that giving rewards has a positive effect on work productivity at CV Jajanan Premium Nusantara, as well as the application of punishment. In addition, giving rewards and punishments together also has a positive influence on work productivity at CV Jajanan Premium Nusantara.